2018
DOI: 10.3390/c4030045
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectrochemical Response of WO3/Nanoporous Carbon Anodes for Photocatalytic Water Oxidation

Abstract: This work demonstrates the ability of nanoporous carbons to boost the photoelectrochemical activity of hexagonal and monoclinic WO3 towards water oxidation under irradiation. The impact of the carbonaceous phase was strongly dependent on the crystalline structure and morphology of the semiconductor, substantially increasing the activity of WO3 rods with hexagonal phase. The incorporation of increasing amounts of a nanoporous carbon of low functionalization to the WO3 electrodes improved the quantum yield of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 61 publications
5
6
0
Order By: Relevance
“…The respective onset potentials (vs. Ag-AgCl) of the WW6 and WU6 photoanodes are 0.41 V and 0.28 V in the presence of SO 3 2– and 0.50 V and 0.48 V in the absence of SO 3 2– , respectively. This is consistent with previous reports on WO 3 -based electrodes ( Ng et al, 2012 , Gomis-Berenguer et al, 2018 , Patil and Patil, 1996 , Costa et al, 2020 , Núñez et al, 2019 ).
Fig.
…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…The respective onset potentials (vs. Ag-AgCl) of the WW6 and WU6 photoanodes are 0.41 V and 0.28 V in the presence of SO 3 2– and 0.50 V and 0.48 V in the absence of SO 3 2– , respectively. This is consistent with previous reports on WO 3 -based electrodes ( Ng et al, 2012 , Gomis-Berenguer et al, 2018 , Patil and Patil, 1996 , Costa et al, 2020 , Núñez et al, 2019 ).
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…(ii) In both light and dark conditions, stable photocurrents were promptly generated at high overpotential (1.2 V vs. Ag-AgCl), and (iii) the quasi-stationary photocurrent increased with applied potential, indicating the inverse effect between charge transfer and bulk recombination processes ( Peter, 2018 , Patil and Patil, 1996 , Peter et al, 2020 ). This is consistent with the data reported previously for the WO 3 /nanoporous carbon composite ( Gomis-Berenguer et al, 2018 ), Fe 2 O 3 ( Li et al, 2021 ), and Fe 2 O 3 /WO 3 ( Muller et al, 2017 ) photoanodes.…”
Section: Resultssupporting
confidence: 93%
“…These results are consistent with previous reports on other types of photoanodes based on BiVO 4 /carbon spheres and WO 3 /nanoporous carbon . Gomis-Berenguer et al , observed a varying trend in the photoelectrochemical response of WO 3 /nanoporous carbon-based photoanodes for photocatalytic water oxidation with different weight ratios of nanoporous carbon, and 20 wt % was found to be the most favorable content of nanoporous carbon. It is noteworthy to mention that the enhanced PEC performance of BT-CN, beyond the intrinsic properties of carbonaceous material, is anticipated not solely due to its typical characteristics but also because of the synergistic photoelectrochemical response arising from the inherent photocatalytic processes exhibited by g-C 3 N 4 . ,, Also, the photoactive nature of g-C 3 N 4 contributes to the observed improvements, creating a distinctive charge accumulation region within the BT-CN composite .…”
Section: Resultssupporting
confidence: 92%
“…Wang et al enhanced the photoelectrochemical water oxidation reaction of the BiVO 4 photoanode by involving carbon spheres, and the photocurrent density and bulk carrier separation efficiency of carbon sphere-modified BiVO 4 were significantly higher than that of pristine BiVO 4 because carbon spheres acted as electron reservoirs, promoting efficient separation of photoexcited charge carriers. The photoelectrochemical performance of hexagonal and monoclinic WO 3 toward water oxidation under light irradiation was boosted by incorporating them with an amorphous nanoporous carbon additive that facilitated the majority carrier transport through the graphitic layers …”
Section: Introductionmentioning
confidence: 99%
“…The increasing cathodic current below 0 V confirms the intercalation of protons into WO 3 crystals to form a tungsten bronze (H x WO 3 ) state. 21,32 In particular, the increased cathodic current and shifts to more positive potential in acidic environment are indicative of conductive H x WO 3 formation. This behavior of the WO 3 electrode is the basis of the pH response and is described by the following equation 16,33 :…”
mentioning
confidence: 99%